P-114 Liver transplantation for non-alcoholic steatohepatitis: outcomes in the main transplant center in Peru - Espinoza, Saúl (2021)
Abstracts of the 2021 Annual meeting of the ALEH (Asociación Latinoamericana para el Estudio del Hígado)